Apoptotic Cell Death and the Proliferative Capacity of Human Breast Cancers - Gabriele A. Losa; Riccardo Graber (Analytical Cellular Pathology)
The proliferative capacity (%S‐phase fraction), DNA ploidy, apoptosis frequency (DNA fragmentation) and steroid hormone receptor status (estrogen receptor, ER; progesterone receptor, PR) of 110 samples of human breast tissues with ductal invasive carcinoma were measured using biochemical and cytofluorimetric procedures. The DNA fragmentation had a left‐skewed frequency distribution and an overall median value of 1.64%, whilst the median %S‐phase fraction was 8%. The median %DNA fragmentation and %S‐phase fraction were 1.96% and 16% in hyperdiploid tumours (n=29; DNA index >1.1) higher than in hypodiploid tumors (n=10; DNA index 0.96), 0.38% and 7.5%. DNA diploid tumours (n=71) had median %DNA fragmentation and %S‐phase values of 1.68% and 6%, consistently lower than the median values of DNA hyperdiploid tumours. The ER content of hypodiploid tumours was about one half (median: 5.9 fmol/mg) the median values in hyperdiploid (10.6 fmol/mg) and diploid tumours (14.6 fmol/mg). This may correlate with the lowest frequency of apoptosis in hypodiploid tumours, at least when measured by biochemical methods which only detect cells in the late phases of apoptosis. In contrast, the median PR was lowest in hyperdiploid tumours than in hypo and/or diploid tumours. The %S‐phase/%fragmented DNA ratio for the hypodiploid tumours was 19.7, significantly higher than the ratios for hyperdiploid (8.2) and diploid tumours (3.6). These findings indicated that there is an imbalance between proliferative capacity and cell death or growth arrest in human breast tumours. This imbalance may well be linked to a loss of steroid hormone control.